The Synergistic Effect of Ascorbic Acid and Selenium on Serum Testosterone in Restraint Stressed Rats - Alaa K. M. Al-amery1 , Ali A. Al-Fahham2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The present study aimed to determine the synergistic effects of ascorbic acid and selenium on serumtestosterone level in male rats exposed to restraint stress . Wistar rats weighting 175±25 grams were dividedrandomly into four equal groups (n=10), some were supplemented with ascorbic acid (50 mg/kg bw/day)orally, the second group was supplemented with selenium (0.02 µg/kg bw/day) orally, third group was orallysupplemented with both ascorbic acid and selenium , the control included ten rats .Blood was collectedon 20th days of experiment, and serum testosterone, and luteinizing hormone (LH) were measured byenzyme-linked immunosorbent assay (ELISA). The results for 20th days showed that supplement of ratswith ascorbic acid has highly significantly (P<0.001) increased serum testosterone to be (5.18 ± 0.1 ng/ml compared to stressed rats which recorded (2.37 ± 0.16 ng/ml) and showed that supplement of rats withselenium has highly significantly (P<0.001) increased serum testosterone level to be (5.28 ± 0.15 ng/ml)compared to stressed rats, and showed that supplement of rats with (ascorbic acid+ Selenium) has highlysignificantly (P<0.001) increased serum testosterone level to be (5.78 ± 0.09 ng/ml) compared to stressedrats which recorded (2.37 ± 0.16 ng/ml). It is probable that there is a synergistic effect of ascorbic acid andselenium in relieving effect on restraint stress on male rats and enhancing testosterone levels .